MRM: mobile resource management scheme on mobile cloud computing - Yi, Gangman; Heo, Yoon-A; Byun, Hwirim; Jeong, Young-Sik (Journal of ambient intelligence and humanized computing, 2018)
Mobile Resource Management without Cloud Server (MRM) is the computing resource integrated management of mobile devices in order to establish mobile cloud computing infrastructure without a cloud server and to provide computing services in this research. The MRM forms a logical resource pool to integrate physical resources from scattered mobile devices and provides computing services. In other words, the MRM offers static and dynamic performance-based computing services, designed to provide computing services that guarantee availability and expandability through a mobile device resource pool without a cloud server. To this end, the MRM defines static and dynamic metadata to manage mobile devices. Detailed schemes consisting of the MRM configuration, the MRM management, and the MRM operation are established to design and implement the MRM. To integrate the MRM resources and validate the effectiveness of the computing services, the configuration time for resource integration, and the task time, in accordance with simultaneous requests for computing services, is measured, and the availability results for the MRM are demonstrated.